Sex Differences and Symptoms of Acute Coronary Syndrome - Tahereh Najafi Ghezeljeh; Mesfin Kassaye Tessma; Azita Emami (Iran University of Medical Sciences, 2015)
Background: The purpose of this study was to examine symptoms of acute coronary syndrom (ACS) with resect to sex differences. Methods: This comparative cross-sectional study was performed on patients older than 20 years with ACS who were hospitalized at cardiac wards. Sampling was performed through stratified sampling on the basis of sex. Five hundred male and female patients met all eligiblity criteria. The questionnaire included demographic, disease characteristics, and the Iranian version of the accompanying symptom checklist. Data collection completed over one year. SPSS version 21 was used for data analyses by using Chi-square test, independent t test and Multiple logistic regression. The level of significance was specified at 0.05. Results: Men reported tiredness (77.2%), weakness (72.4%), diaphoresis (70.0%) and anxiety (83.6%) as their most frequent symptoms. For women, the most frequently chosen symptoms were anxiety (94.8%), tiredness (90.0%), palpitation (85.2%), and weakness (82.8%). Statistically significant differences were observed between women and men with regard to symptoms. Multiple logistic regression indicated that sex was the most important explanatory variable, which is independently associated with different symptoms. Conclusion: According to the results, significant differences were observed between women and men regarding ACS symptoms. The major implication of this investigation is the need for accurate cardiac assessment according to sex. Further research should investigate the nature and consequences of sex differences in language use of initial presentation with coronary symptoms, through the referral process.